Assessing caregiving experience in COPD: Content validity of the Zarit Burden Interview in Canadian and Portuguese caregivers - Selzler, Anne-Marie (2022)
Informal caregivers play an important role in chronic disease management but their experience is often neglected. The objective of this study was to explore the content validity of the Zarit Burden Interview (ZBI) in caregivers of individuals with COPD in Canada and Portugal.